QSO MUSEUM - II. Search for extended Lyα emission around eight z ∼ 3 quasar pairs - Herwig, Eileen; Battaia, Fabrizio Arrigoni; Lobos, Jay González; Farina, Emanuele P.; Man, Allison W. S.; Bañados, Eduardo; Kauffmann, Guinevere; Cai, Zheng; Obreja, Aura; Prochaska, J. Xavier (Astronomy and astrophysics, 2024)
Extended Lyα emission is routinely found around single quasars across cosmic time. However, few studies have investigated how such emission changes in fields with physically associated quasar pairs, which should reside in dense environments and are predicted to be linked through intergalactic filaments. We present VLT/MUSE snapshot observations (45 minutes/source) to unveil extended Lyα emission on scales of the circumgalactic medium (CGM) around the largest sample of physically associated quasar pairs to date, encompassing eight pairs (14 observed quasars) at z ∼ 3 with an i-band magnitude between 18 and 22.75, corresponding to absolute magnitudes Mi(z = 2) between −29.6 and −24.9. The pairs are either at close (∼50-100 kpc, five pairs) or wide (∼450-500 kpc, three pairs) angular separation and have velocity differences of Δv ≤ 2000 km s−1. We detected extended emission around 12 of the 14 targeted quasars and investigated the luminosity, size, kinematics, and morphology of these Lyα nebulae. On average, they span about 90 kpc and are 2.8 × 10 43 erg s−1 bright. Irrespective of the quasars’ projected distance, the nebulae often (∼45%) extend toward the other quasar in the pair, leading to asymmetric emission whose flux-weighted centroid is at an offset position from any quasar location. We show that large nebulae are preferentially aligned with the large-scale structure, as traced by the direction between the two quasars, and conclude that the cool gas (10 4 K) in the CGM traces well the direction of cosmic web filaments. Additionally, the radial profile of the Lyα surface brightness around quasar pairs can be described by a power law with a shallower slope (∼−1.6) with respect to single quasars (∼−2), indicative of increased CGM densities out to large radii and/or an enhanced contribution from the intergalactic medium (IGM) due to the dense environments expected around quasar pairs. The sample presented in this study contains excellent targets for ultra-deep observations to directly study filamentary IGM structures in emission. This work demonstrates that a large snapshot survey of quasar pairs will pave the way to direct statistical study of the IGM.
Online veröffentlicht: 15. November 2024
Gesehen am 06.06.2025